Plasma Inflammatory Markers and Ventriculostomy-Related Infection in Patients With Hemorrhagic Stroke: A Retrospective and Descriptive Study - Bögli, Stefan Yu; Wang, Sophie S.; Pietrzko, Elisabeth; Müller, Achim; Eisele, Amanda; Keller, Emanuela; Brandi, Giovanna (Frontiers in Neurology, 2022)
Background Diagnosis of ventriculostomy-related infection (VRI) remains difficult due to the various existing definitions. In patients with hemorrhagic stroke, its diagnosis might be further complicated by the presence of intraventricular blood. Furthermore, hemorrhagic stroke per se may cause symptoms compatible with VRI. This study aimed to evaluate the benefit of plasma inflammatory markers for the diagnosis of VRI and its differentiation from patients with non-cerebral infection and patients without infection in a cohort of patients with hemorrhagic stroke. Methods A total of 329 patients with hemorrhagic stroke and an external ventricular drain (EVD) in situ were admitted to the Neurocritical Care Unit, University Hospital Zurich over a period of 6 years. Of those patients, 187 with subarachnoid hemorrhage and 76 with spontaneous intracerebral hemorrhage were included. Patients with VRI were compared to patients without any infection and to patients with non-cerebral infection, with regards to their clinical characteristics, as well as their inflammatory plasma and cerebrospinal fluid (CSF) markers. For the analysis, peak values were considered. Results The VRI was diagnosed in 36% of patients with subarachnoid and in 17% of patients with intracerebral hemorrhage. The VRI was diagnosed on an average day 9±6.2 after EVD insertion, one day after the white blood cell count (WBC) peaked in CSF (8 ± 6.3). Plasma inflammatory markers (WBC, C-reactive protein “CRP” and procalcitonin “PCT”) did not differ among patients with VRI compared to patients without infection. The CRP and PCT, however, were higher in patients with non-cerebral infection than in patients with VRI. The WBC in CSF was generally higher in patients with VRI compared to both patients without any infection and patients with non-cerebral infection. Conclusions No differences in plasma inflammatory markers could be found between patients with VRI and patients without any infection. Conversely, CRP/PCT were higher in patients with non-cerebral infection than in patients with VRI. Altogether, CRP, PCT, and WBC are not suitable parameters for VRI diagnosis in neurocritical care unit patients.